Regionally infused lidocaine can dose-dependently protect the ischemic spinal cord in rabbits and may be associated with the EAA changes. (23rd April 2020) - Liu, Linwen; Xu, Yongfu; Zhou, Yachun; Li, Shitong; Yao, Junyan
Highlights: Lidocaine regional perfusion through abdominal aorta attenuates spinal cord IRI. Lidocaine treatment has a dose-dependent neuroprotective effect. The inhibition of EAAs release may be one of the mechanisms involved. Abstract: Objective: In our previous study, we found that lidocaine, infused through the abdominal aorta, could protect the spinal cord against the ischemia-reperfusion (I/R) injury caused by aortic occlusion. However, whether lidocaine protective effects have dose-dependent properties and its underlying mechanisms still remain unclear. This study was designed to investigate whether regionally infused lidocaine could dose-dependently protect spinal cord against I/R injury in rabbits and its underlying mechanism. Methods: 46 New Zealand white rabbits were randomized into six groups: Group NS (normal saline control); Group L10 (lidocaine 10 mg/kg); Group L20 (lidocaine 20 mg/kg); Group L40 (lidocaine 40 mg/kg); Group L80 (lidocaine 80 mg/kg) and Group Sham. In Group NS, Group L10, Group L20, Group L40 and Group L80, spinal cord ischemia was induced by infrarenal aortic occlusion for 30 min. The sham group did not receive spinal cord ischemia. During the occlusion, normal saline or lidocaine at different doses was infused continuously through a catheter into the clamped abdominal aorta respectively. Neurologic behavior functions were assessed according to the Tarlov scale system at the moments of 0, 6, 24 and 48 h after reperfusion. The neural injuries were evaluated by the histological examination and the count of normal α-motor neurons in the ventral horn. The levels of excitatory amino acids (EAAs) in the spinal cord, including glutamate (Glu) and aspartic acid (Asp), were analyzed by high performance liquid chromatography with fluorescence detection. Results: The Tarlov scales in the Group L20 and the Group L40 were significantly higher than those in the Group NS at 24 and 48 h after reperfusion ( P < 0.05). 12.5 % animals in Group L40 and 25 % animals in Group L20 were paraplegic versus 75 % animals in Group NS at 48 h after reperfusion ( P < 0.05). The median of normal α-motor neurons in the L20, L40 and L80 groups was 7.5, 9 and 5 respectively which was significantly higher than in the NS group (count 0, P < 0.05). The levels of L-ASP and L-Glu remarkably decreased in the Group L10 and the Group L40 compared to Group NS ( P < 0.05). Conclusions: These data revealed that regional administration of lidocaine through the abdominal aorta can provide dose-dependent protection on spinal cord I/R in rabbits. Inhibition of EAA release may be one of the underlying mechanisms.